(Hetero)aryl substituted thiazol-2, 4-yl scaffold as human carbonic anhydrase I, II, VII and XIV activators. (1st January 2019) - Rami, Marouan; Winum, Jean-Yves; Supuran, Claudiu T.; Melnyk, Patricia; Yous, Saïd
Abstract: Using histamine as lead molecule, a library of (hetero)aryl substituted thiazol-2, 4-yl derivatives incorporating pyridine as proton shuttling moiety were obtained and investigated as activators of human carbonic anhydrase (CA, EC 4.2.1.1) isoforms I, II, VII and XIV. Some derivatives displayed good activating and selectivity profiles. This study provides an interesting opportunity to study the thiazole scaffold for the design of CA activators (CAAs), possibly acting on the central nervous system and targeting pathologies involving memory and learning impairments.